Helping a Few a Lot or Many a Little: Political Ideology and Charitable Giving - Farmer, Adam; Kidwell, Blair; Hardesty, David M. (Journal of Consumer Psychology, 2020)
The authors examine political ideology as it influences how people distribute their donations across multiple charities. Findings from five studies indicate that liberals and conservatives donate similar overall amounts of money; however, liberals tend to give to a greater number of charities, people, and causes overall while giving less to each (breadth). Conservatives tend to donate to fewer charities, people, and causes overall while giving more to each (depth). Using the model of moral motives, conservatives’ endorsement of social order led to their focus on smaller groups and protecting members of these groups as they give with depth. In contrast, liberals’ endorsement of social justice led to their focus on eliminating broad inequality as they give with breadth. However, these ideological tendencies can be reversed as conservatives gave with breadth when protecting social order and liberals gave with depth when equality was restored.